An Investigation Of Student's Experience Joining English Tutorial Program (Etp) At Universitas Muhammadiyah Surakarta - Jati Sutami, Pebri; , Fitri Kurniawan, M. Res, Ed (2017)
This study is aimed to investigate the student's experience joining English Tutorial Program (ETP) at Universitas Muhammadiyah Surakarta. In achieving the objectives, the researcher used hermeneutic phenomenological study as an approach to collect and analyze the data. The researcher recruited a female first semester accounting education student who joining English Tutorial Program (ETP) at Universitas Muhammadiyah Surakarta to participant in the research. The technique for collecting data is repeated semi-structured in depth-interview as data collection. The result of the analysis shows that the researcher found 4 findings in the student's experience joining ETP;1)The student assumes that ETP can improve English skills, 2)The ETP tutors employ interesting teaching methods, 3)The place used for ETP is problematic, 4)The quality of the program should be improved. Keywords: hermeneutic phenomenology, student's experience, English Tutorial Program (ETP), Universitas Muhammadiyah Surakarta.